Answers

2015-03-15T13:32:26+05:30

given : distance between the foot of the tree and the broken part of the tree that touches the ground = 30 m 
let , 
the height of standing part of the tree be = h 
the height of  fallen part (forms hypotenuse) be = x
then the total height of the tree will be = h + x 
now, 
tan 30 = h/30 m
     1/√3 = h/30 m 
    30/√3 = h
    ⇒ h= 30/√3 m           ..... 1
similarly, 
cos 30 = 30 m/ x 
   √3/2 = 30 / x
√3x = (30)2 
 √3x = 60 m 
⇒ x = 60 / √3 m           ......2
       ( we now have both value of h and x )
   on adding equation1 & 2 :
 ⇒ h + x = 30 /√3 +60 /√3
         =90 /√3 m 
         = 60√3 m
so , the total height of the tree is 60√3 m .
1 5 1
any queries,.. leave a comment below,.. n dont forget to rate